ROLE OF CONTAMINATED FRUITS IN THE TRANSMISSION OF INTESTINAL PARASITES IN KHARTOUM CENTRAL MARKET-KHARTOUM STATE (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Fruits play an important role in transmission of parasitic diseases to human in Khartoum. So, increasing consumer awareness about the risks factors associated with consumption of raw fruits is very important. Education on food hygiene should be  strengthened  to  change  unhealthy  dietary  habits  and  ensure  safe  daily food  consumption.  This  study  was  conducted  at Khartoum central market, in Khartoum state-Sudan to detect the parasitic contamination of fruits. Microscopic examination of the samples was carried out after washing the fruits by formal saline and then examining the sediment after centrifugation using wet preparation. A total of 233 samples of fruits were collected randomly, with six types of fruits included (apple, banana, mango, orange, grape and guava), during the period from December 2017 to April 2017. Among the 233 samples, forty three 43 (18.5%) samples were positive for intestinal parasites. Among positive samples, banana and apple were found to have the highest parasitic prevalence.  The parasites  identified were  insects, S. stercoralis, E. coli, E. histolytica,  Taenia spp, Ascaris, Schistosoma,  H. diminuta and Hookworms. The results showed that Insects were the most prevalent as they were detected in 11 samples.